L1 incidence reflects pelvic incidence and lumbar lordosis mismatch in sagittal balance evaluation. Issue 30 (July 2018) - Choi, Sung Hoon; Son, Seung Min; Lee, Dong-Ho; Lee, Choon Sung; Shin, Won Chul; Hong, Chul Gie; Lee, Jung Sub; Hwang, Chang Ju
Abstract : Abstract: Retrospective study. To investigate the radiologic and geometrical association between L1 incidence (L1I) with pelvic incidence/lumbar lordosis (PI/LL) mismatch and T1 incidence (T1I) with PI/LL/thoracic kyphosis (TK) mismatch. The relationship between PI and LL is not clear, and it might be because of the absence of a direct radiologic parameter to represent PI/LL mismatch. To the best of our knowledge, this is the first report on a direct radiologic parameter for representing PI/LL mismatch. This study is a retrospective review of 146 patients who underwent anteroposterior and lateral standing radiographs of the whole spine. L1I was defined as the angle between the line perpendicular to the L1 upper endplate and the line connecting the midpoint of the sacral endplate to the center of both femoral heads. T1I was defined as the angle between the line perpendicular to the T1 upper endplate and the line connecting the midpoint of the sacral endplate to the center of both femoral heads. Both were validated using the Pearson correlation coefficient and linear regression analysis. Radiologically measured L1I and T1I were coterminous with calculated measurements of ΔPI/LL and ΔPI/LL/TK in terms of means and standard deviations, respectively. Excellent correlations were found between L1I and ΔPI/LL, and T1I and ΔPI/LL/TK ( R  = 0.997, P  < .01; R  = 0.981, P  < .01, respectively). In linear regression analysis, the slope and intercept of L1I were 0.991 and −0.041, with a predictability of 99.4% ( R 2  = 0.994), and those of T1I were 0.990 and −0.026, with a predictability of 99.0% ( R 2  = 0.990), respectively. L1I and T1I were strongly correlated with PI/LL mismatch and PI/LL/TK mismatch, respectively. L1I and T1I are direct parameters that represent PI/LL mismatch and PI/LL/TK mismatch. They would be useful in analyzing sagittal balance. Level of evidence: Level 3